1995
DOI: 10.1177/096914139500200405
|View full text |Cite
|
Sign up to set email alerts
|

Compliance after 17 Years of Breast Cancer Screening

Abstract: A substantial proportion of eligible women can be committed to mammography every two years, possibly even after reaching the age of 70, if the age at entry is around 50 and the screening programme is well established in the community. Starting a screening programme in older women seems ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…In a longitudinal analysis of nine screening rounds in the Dutch screening programme, 26 only 5% of women who attended the initial screen did not attend any subsequent screening rounds. These women do not benefit from the long term reduction in risk associated with mammographic screening.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal analysis of nine screening rounds in the Dutch screening programme, 26 only 5% of women who attended the initial screen did not attend any subsequent screening rounds. These women do not benefit from the long term reduction in risk associated with mammographic screening.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study of 6,898 women found that unpleasant mammography experiences, such as enduring more pain than anticipated or being dissatisfied with the technique of the screening staff, was negatively correlated with return for future mammography (Scaf-Klomp, van Sonderen, Stewart, van Dijck, & van den Heuvel, 1995). In addition, a body of information has formed regarding patient preferences for learning about the results of their mammograms.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also found a falsepositive mammogram to be associated with a lower compliance with rescreening (6,9,11,34), including one conducted within the OBSP (35). However, a recent metaanalysis reported that although Canadian women were less likely to return for routine screening after a false-positive mammogram, women in the United States were more likely and European women were equally likely to return (36).…”
Section: Discussionmentioning
confidence: 90%